Variability of Titan's induced magnetotail: Cassini magnetometer observations. Issue 3 (31st March 2014) - Simon, Sven; Neubauer, Fritz M.; Wennmacher, Alexandre; Dougherty, Michele K.
Abstract We study the structure and variability of Titan's magnetotail by analyzing Cassini magnetic field observations from all tail crossings between 2005 and 2013. Titan's magnetotail is strongly affected by fluctuations in the ambient magnetospheric field conditions. Therefore, even Titan flybys with nearly identical trajectories may reveal a completely different location and strength of the perturbations in the moon's tail. Short‐scale variations of the ambient magnetospheric field may cause a "fragmentation" of Titan's magnetic lobes, as also seen in Cassini Plasma Spectrometer ion data. By transforming the magnetic field perturbations detected during all available tail crossings to the Draping Coordinate System, we identified the following general characteristics of Titan's plasma interaction: (1) Perpendicular to the background magnetic field and the corotation direction, Titan's magnetotail is confined to a narrow region with a diameter of about 5 Titan radii. Thus, Titan's tail exhibits a rather "flat" structure reminiscent of a delta wing. (2) The plasma incident upon Titan does not possess a significant velocity component along the Saturn‐Titan line. (3) The nonzero component of the background field along the corotation direction generates an asymmetry of Titan's magnetotail which clearly manifests in Cassini magnetometer data.